Deskripsi Pemanfaatan Sarana Menurut Peserta dalam Pelatihan Menjahit di Dinas Tenaga Kerja dan Perindustrian Kota Padang - Naufita, Sawiti; Sunarti, Vevi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was motivated by the success of the sewing training program at the Manpower and Industry Office of the City of Padang. This was proven by 20 participants in the sewing training held by around 17 participants who had successfully opened their own businesses, namely sewing business, while 3 others still worked with other people but they already had sewing skills. The researcher suspects the cause of the success of the program implemented by the institution is by utilizing sewing training facilities. This study aims to look at the description of the use of facilities according to participants in sewing training at the Padang City Manpower and Industry Office. This type of research is quantitative descriptive research. The population in this study were all participants who participated in sewing training totaling 20 people. The sampling technique used is Stratified Random Sampling. Samples were taken as much as 75% of the population so there were 15 people. The technique of collecting data uses a questionnaire. While the statement collection data collection tool. The data analysis technique uses the percentage formula. The results showed that the use of facilities according to participants in sewing training at the Department of Manpower and Industry in Padang City was (a) utilization of facilities according to participants in sewing training in terms of availability carried out very well (b) utilization of facilities according to participants in sewing training in terms of adequacy was carried out very well (c) utilization of facilities according to participants in the sewing training in terms of the quality carried out very well. This is evidenced by the majority of participants always giving statements. Based on the results of the research, it is recommended that the institution continue to improve the success of the training program and maintain the use of sewing training facilities at the Padang City Manpower and Industry Office.